Comparison of two anthropomorphic test devices using brain motion. (December 2018) - Koncan, David; Post, Andrew; Gilchrist, Michael; Hoshizaki, Thomas Blaine
The use of anthropomorphic test devices in head impact biomechanics research is common; however, each device has unique properties based on its construction. When conducting reconstructions, choice of head form is at the discretion of the researcher. In addition, different data collection methods are often used. The influence of different test devices can affect comparisons between studies, as each device elicits different impact responses due to different physical properties. This study describes a method of comparison for anthropomorphic test devices based on finite element response of brain motion. Occipital impacts were conducted on a monorail drop rig, following impact parameters similar to a cadaveric impact that has been used for validation of finite element models of the brain. Two commonly used anthropomorphic test devices, the Hodgson-WSU and Hybrid III, were impacted. These head forms were evaluated by dynamic responses, brain motion via neutral density target traces, and maximum principal strain for two impact velocities. The Hybrid III head form showed lower magnitude results compared to the Hodgson-WSU for peak linear and rotational accelerations, rotational velocity, maximum principal strain, and neutral density target excursions. The smallest differences in response were 11% for peak linear acceleration with differences in neutral density target excursions reaching 60%. Maximum principal strain is suggested as the most comparable metric between anthropomorphic test devices after peak linear acceleration, with expectation of lower responses from the Hybrid III as compared to those of the Hodgson-WSU.